Recursos naturales y crecimiento económico en América Latina (1980-2014) - Ticona Calderón, Deysi Estefany (2020)
Disparities in per capita income levels among economies around the world have motivated various investigations and approaches to model the behavior of economic growth in the long term. A pattern that has been evident among the countries poor in natural resources has been its pronounced economic growth in comparison to the countries rich in natural resources. In this context, the need arises to objectively evaluate the repercussions of dependence on natural resources in Latin American countries, in order to identify the variables that are directly affected by this dependency. The objective of this research is to analyze the impact of natural resources on the economic growth of 17 Latin American countries, using the Solow-Swan economic growth model as a theoretical basis, using the panel data estimation technique for the period 1980-2014 with a five-year periodicity, using the Generalized Least Squares (GLS) method. The variables used in this analysis were the Gross Domestic Product (GDP) per capita and initial per capita, fertility rate, aggregate investment, exports of natural resources, concentration of exports, institutional quality and the GDP gap. No evidence of negative correlation was found between the natural resources sector and the economic growth rate, therefore no evidence of the existence of the Dutch disease was found during the study period. It was also shown that the negative association between growth and natural resources is explained by the concentration of primary exports. Furthermore, the existence of conditional convergence between the sample countries was verified. This finding is robust, since after introducing the control variables, the level of significance and the sign of the convergence indicator did not change. Likewise, the speed of convergence found was 1.35%, close to the 1.41% obtained by De Gregorio & Lee (1999) for Latin American countries. Finally, it was shown that institutional quality negatively affects the relationship between the level of concentration of exports and economic growth.